Risk factors and prediction model for mental health in Chinese soldiers - Zhao, Mengxue; He, Ying; Tang, Quan; Wang, Ni; Zheng, Haoxin; Feng, Zhengzhi (Frontiers in Psychiatry, 2023)
Introduction: This study aimed to explore potential risk factors for mental health concerns, and the prediction model for mental health concerns in Chinese soldiers was constructed through combined eligible risk factors. Methods: This cross-sectional surgery was performed in direct command from Gansu, Sichuan, and Chongqing in China, and soldiers were selected by cluster convenient sampling from October 16, 2018, to December 10, 2018. The symptom checklist 90 (SCL-90) and 3 questionnaires (military mental health status questionnaire, military mental health ability questionnaire, and mental quality questionnaire for army-men) were administered, including demographics, military careers and 18 factors. Results: Of 1,430 Chinese soldiers, 162 soldiers presented mental disorders, with the prevalence of 11.33%. A total of 5 risk factors were identified, including serving place (Sichuan vs Gansu: OR, 1.846, 95%CI: 1.028-3.315, P=0.038; Chongqing vs Gansu: OR, 3.129, 95%CI, 1.669-5.869, P=0.003), psychosis (OR, 1.491, 95%CI, 1.152-1.928, P=0.002), depression (OR, 1.482, 95%CI, 1.349-1.629, P<0.001), sleep problems (OR, 1.235, 95%CI, 1.162-1.311, P<0.001), and frustration (OR, 1.050, 95%CI, 1.015-1.087, P=0.005). The area under the ROC curve through combined these factors was 0.930 (95%CI: 0.907-0.952) for predicting mental disorders in Chinese soldiers. Conclusion: The findings of this study found the mental disorders, onset in Chinese soldiers can be predicted on the basis of 3 questionnaires, and the predictive value of combined model was high.